2007
DOI: 10.1117/12.726032
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography for art conservation and archaeology

Abstract: Optical coherence tomography (OCT) is a fast scanning Michelson interferometer originally designed for in vivo imaging of the eye. In 2004, our group along with two other groups first reported the application of OCT to art conservation and archaeology. Since that time we have been conducting a project to investigate systematically the potential of OCT as a new tool for non-invasive examinations of a wide range of museum objects and to design an OCT optimised for in situ use in museums. Here we present the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Some of the ancient glass artefacts from the collections of the British Museum have been examined by Liang et al [17,34,37]. These studies confirmed the ability of OCT to reveal details of the internal structure of the glasses up to 0.5 mm under the surface.…”
Section: Examination Of the Structure And State Of Preservation Of Pasupporting
confidence: 62%
See 2 more Smart Citations
“…Some of the ancient glass artefacts from the collections of the British Museum have been examined by Liang et al [17,34,37]. These studies confirmed the ability of OCT to reveal details of the internal structure of the glasses up to 0.5 mm under the surface.…”
Section: Examination Of the Structure And State Of Preservation Of Pasupporting
confidence: 62%
“…This trade-off must therefore always be taken into account when new experiments are under consideration. An important account of this subject has also been presented by Liang et al [34].…”
Section: Examination Of the Structure And State Of Preservation Of Pamentioning
confidence: 97%
See 1 more Smart Citation
“…A related and notable development of recent years is the depth selective variant of NIR-based imaging called Optical Coherence Tomography (OCT) [47,48]. OCT is a point scanning system based on the use of a NIR source coupled to a Michelson interferometer.…”
Section: Methods Based On Infrared Radiationmentioning
confidence: 99%
“…OCT gives not only the subsurface layer structures but also reveals the scattering and absorption properties of the material [62]. OCT complements spectral imaging in the identification of the material and providing information on the surface topology and subsurface layer structure.…”
Section: Combined With Optical Coherence Tomography (Oct)mentioning
confidence: 99%